Autologous Hematopoietic Cell Transplant as an Effective Treatment Modality for Systemic Sclerosis and Multiple Myeloma - Memon H; Parrondo R; Schreurs J; Ayala E; Iqbal M (Journal of Blood Medicine)
Hamda Memon,1 Ricardo Parrondo,2 Julianna Schreurs,2 Ernesto Ayala,2 Madiha Iqbal2 1Department of Family Medicine, Geisinger Health in Wilkes Barre, Wilkes Barre, Pennsylvania, USA; 2Division of Hematology and Oncology, Mayo Clinic, Jacksonville, Florida, USACorrespondence: Madiha Iqbal, Department of Medicine,Division of Hematology-Oncology and Blood and Marrow Transplantation Program, Mayo Clinic, 4500 San Pablo road, Jacksonville, FL, 32224, USA, Email Iqbal.madiha@mayo.eduAbstract: Systemic sclerosis (SSc) is a multi-system disease characterized by a dysregulated immune system. Autologous hematopoietic cell transplantation (AHCT) is the only treatment that has been shown to confer significant benefit in controlling disease and improving survival for patients with SSc. A diagnosis of multiple myeloma (MM) after the diagnosis of SSc is rare and optimal treatment in such cases remains unclear. We here report a case of a female patient who was diagnosed with MM while she was undergoing evaluation for AHCT due to SSc. A novel conditioning regimen for AHCT, with therapeutic efficacy in SSc and MM was offered to the patient, resulting in long term remission of both diseases.Keywords: systemic sclerosis, autologous hematopoietic cell transplantation, multiple myeloma